Impact Of Horizontal Load On Shield Supports - Thomas M. Barczak (International Conference on Ground Control in Mining, 1984)
A theoretical evaluation of the impact of horizontal load on shield support capacity is made from a static rigid body analysis of the shield structure. Parameters affecting horizontal support resistance are investigated for a typical too-leg shield design. Horizontal forces acting on a roof support element are found to be both roof-generated and shield-generated. The impact of shield-generated horizontal forces on roof strata is also discussed from a theoretical viewpoint in relation to desired ground control. A technique is described whereby horizontal loading of shield supports can be measured underground. Horizontal load measurements from two different longwall faces were found to be significant, ranging from 20-35 pct of measured vertical load.